Alternativas de controle químico do arroz-vermelho e persistência dos herbicidas (imazethapyr + imazapic) e clomazone na água e no solo - Santos, Fernando Machado dos (2006)
Weed infestation, mainly with red rice (Oryza spp.), is the most important factor limiting yield increase in paddy rice in Rio Grande do Sul state. Chemical red rice control is the most used tool in this area. But, its use can originate herbicide residue in water and soil that can cause carry-over to rotational crops and environmental contamination. To assess these possible problems it was carry a two year experiment with the objective of: 1) to evaluate the efficiency of two alternatives (Clearfield system and the use of clomazone with seed protector) on red rice control; and 2) to evaluate imazethapyr and clomazone field persistence in water and soil and 3) evaluate the herbicides carry over to non-tolerant crop. In the first year (2004/05) IRGA 422 CL rice cultivar was drill seeded in the experimental area located in Santa Maria, RS, Brazil, to evaluate red rice control by seven treatments including rates and timing of (imazethapyr + imazapic) and clomazone aplication. After rice harvest, burndown herbicide was applied, and it was planted riegrass in winter 2005, and non-tolerant rice was seeded in 2005/06 growing season, aiming to evaluate the carry over effects of herbicides. The results showed that the Clearfield system is more efficient in red rice control than clomazone. The application of 0,7 L ha-1 (imazethapyr + imazapic) PRE followed by the same rate at POS, promoted 100% red rice control, withou reducing rice grain yield (cultivar IRGA 422 CL). The experiment showed also that, between the evaluated treatments, the split application of (imazethapyr + imazapic), was the most persistent in rice paddy water. It was observed carryover effects of (imazethapyr + imazapic) in the non-tolerant rice, causing yield reduction in IRGA 417 variety seeded one year after herbicide application. Clomazone did not have carryover effects one year after the application. Ryegrass did not showed injury to the herbicide residues in soil.